PENYELESAIAN KONFLIK TOKOH UTAMA DALAM NOVEL LAWA KARYA SAIDUL TOMBANG - Yulna Pilpa Sari; Sayfrial '; Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: Novel Lawa is the first novel of the work of the artist and journalist from Kampar ie Saidul Tombang. This novel tells the life of a married couple who are not blessed with a child with a cultural background Kampar. This research was motivated by the author's interest in exploring the story of the cultural background that is rarely explored Kampar artists but should be much in demand. This study discusses the Conflict Resolution in Lawa Novel Saidul Tombang work. This study also discusses the causation internal conflict and external conflict are found in the novel Lawa created by Saidul Tombang. This study used a qualitative approach and descriptive method that aims to describe or illustrate how the settlement of internal conflict and external conflict in the novel Lawa Tombang Saidul work. Data collection techniques in this study is the engineering documentation, ie reading books related to the problems examined. Technical analysis of the data is to identify the research data, describe the results of research, interpret and summarize the results of research. Results of the research is a conflict of classification internal / external, causes of conflict internal / external, due to the conflict internal / external and internal conflict resolution / external found in Lawa novel Tombang Saidul work. The results of this study as well as a form documenting the existing conflict resolution in the novel Lawa created by Saidul Tombang.Key Words: Confllicts Resolution, Internal Conflict, External Conflict, Novel Lawa.